Amidation of glutamate residues in mycobacterial peptidoglycan is essential for cell wall cross-linking - Shaku, Moagi T.; Ocius, Karl L.; Apostolos, Alexis J.; Pires, Marcos M.; VanNieuwenhze, Michael S.; Dhar, Neeraj; Kana, Bavesh D. (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacteria assemble a complex cell wall with cross-linked peptidoglycan (PG) which plays an essential role in maintenance of cell wall integrity and tolerance to osmotic pressure. We previously demonstrated that various hydrolytic enzymes are required to remodel PG during essential processes such as cell elongation and septal hydrolysis. Here, we explore the chemistry associated with PG cross-linking, specifically the requirement for amidation of the D-glutamate residue found in PG precursors. In Mycobacterium smegmatis, we confirmed the essentiality for D-glutamate amidation in PG biosynthesis by labelling cells with synthetic fluorescent PG probes carrying amidation modifications. We also used CRISPRi targeted knockdown of genes encoding the MurT-GatD complex, previously implicated in D-glutamate amidation, and demonstrated that these genes are essential for mycobacterial growth. We show that MurT-rseGFP co-localizes with mRFP-GatD at the cell poles and septum, which are the sites of cell wall synthesis in mycobacteria. Furthermore, time-lapse microscopic analysis of MurT-rseGFP localization, in fluorescent D-amino acid (FDAA)-labelled mycobacterial cells during growth, demonstrated co-localization with maturing PG, suggestive of a role for PG amidation during PG remodelling and repair. Depletion of MurT and GatD caused reduced PG cross-linking and increased sensitivity to lysozyme and -lactam antibiotics. Cell growth inhibition was found to be the result of a shutdown of PG biosynthesis mediated by the serine/threonine protein kinase B (PknB) which senses uncross-linked PG. Collectively, these data demonstrate the essentiality of D-glutamate amidation in mycobacterial PG precursors and highlight the MurT-GatD complex as a novel drug target.